Investigation of Serum allergen-specific IgE concentrations in feline asthma: a clinical experience - Keskin Yılmaz, N; Kahraman, D; Albasan, H (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of this study is to investigate allergen agents by allergen-specific serum IgE analysis in domestic cats diagnosed with feline asthma (FA). A total of 21 cats (16 FA and 5 control cats) were included in the study. Allergen-specific serum IgE levels were measured in cats diagnosed with feline asthma and in the control group. Allergen levels were classified as negative, weak, moderate and strong. The difference between the two groups was compared statistically. While the mean age of the cats in the FA group was 3.9kg ±2.4 years, the mean age of the cats in the control group was 3.4±2.2 years. The most common clinical manifestations in cats with FA were cough, sneezing, wheezing, and acute dyspnea, respectively. Allergen-specific IgE levels tested for 20 different allergens showed that 14 out of 16 cats developed a reaction to more than one allergen. The vast majority of cats with FA had a moderate or strong positive reaction to house dust mites. In conclusion, FA is an important and common chronic lower respiratory tract disease of feline patients and allergen-specific serum IgE levels can be easily used in clinical practice to guide the selection of allergens in the treatment of this disease and adjust for the quality of life and well-being of cats.